Efficacy of combination therapy with omeprazole, amoxicillin and clarithromycin for treatment of patients with Helicobacter pylori associated gastritis and duodenal ulcer disease - Yeşim ERALP; Can DAVUTOĞLU; Hülya UZUNİSMAİL and Ergun OKTAY (Turkish Journal of Gastroenterology, 2019)
-